Evaluating Alpha-Glucosidase Inhibitory Activity and Toxicity of Cacao Pod Husk (Theobroma cacao L.) Fractions - Iwan Sariyanto; Hartanti (Universitas Pendidikan Mandalika, 2025)
This study aimed to evaluate the anti-diabetic and cytotoxicity potential of ethyl acetate and acetone fractions from cocoa pod husk (Theobroma cacao L.). The cacao pod husks were extracted and fractionated using ethyl acetate and acetone solvent. The alpha-glucosidase inhibitory activity was determined using Saccharomyces cerevisiae alpha-glucosidase with p-nitrophenyl-α-D-glucopyranoside (pNPG) substrate. Toxicity was evaluated against Artemia salina larvae to determine the Lethal Concentration (LC50). The results showed that the ethyl acetate fraction and acetone fraction had LC50 values of 202.31 ppm and 360.07 ppm, respectively, indicating potential cytotoxic activity. Both fractions demonstrated weak alpha-glucosidase inhibitory activity, with inhibition percentages below 50% at the highest tested concentration (60 ppm), preventing the determination of IC50 values. These findings suggest that while the fractions possess bioactive potential indicated by toxicity, they may not be effective alpha-glucosidase inhibitors under the tested conditions.